Implementation of a Professional Competence Development Training Program for Teachers - Andi Ratu Ayuashari Anwar; Nanang Hermawan; By Tri Agung Nusantara Kr.J. Tompong (Universitas Cokroaminoto Palopo, 2026)
This study examines the implementation of a training (diklat) program for developing teachers’ professional competence at SMPN 7 Makassar. The problem addressed in this research concerns how training programs improve teachers’ professional skills and the challenges arising in applying training outcomes in classroom practice. The objective of the study is to analyze the impact of professional development training on teachers’ competence, identify implementation barriers, and evaluate the effectiveness of project-based and technology-based training methods supported by school management. This research employed a qualitative approach with nine teachers of SMPN 7 Makassar who participated in the diklat program as research subjects. Data were collected through classroom observations, semi-structured interviews, questionnaires, and document analysis, including lesson plans, teaching modules, and assessment instruments. The research instruments consisted of observation sheets, interview guidelines, questionnaires, and documentation checklists. Data analysis was conducted using interactive qualitative analysis, encompassing data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation of sources and techniques by comparing findings from questionnaires, interviews, observations, and documentation. The findings indicate that the training program has a positive impact on teachers’ professional competence, particularly in lesson planning, classroom management, preparation of teaching modules, use of diagnostic assessment, technology integration, and implementation of project-based learning. Teachers demonstrated improved understanding of students’ characteristics and applied more creative instructional strategies, such as entrepreneurship projects integrated into learning activities. However, the implementation of training outcomes faces several challenges, including limited time, inadequate facilities, funding constraints, and varying levels of teachers’ technological skills, especially among senior teachers. Overall, the study concludes that the training program effectively enhances teachers’ professional competence, although its sustainability and long-term impact depend on strong institutional support, adequate infrastructure, and continuous assistance to bridge the gap between training and classroom practice.